(untitled) (Journal of the College of Basic Education, 2022)
The present paper aims at investigating themes of war and violence in Naomi Wallace’s No Such Cold Thing. The play symbolizes a unique production of In-Yer-Face theatre that is pioneered by British Dramatist Sarah Kane during the last years of Twentieth century. Wallace’s No Such Cold Thing manipulates the war initiated by United States of America against Afghanistan and the violence sequences of this war on Afghan individuals and American soldiers as well.